2016
DOI: 10.1007/s00380-016-0804-3
|View full text |Cite
|
Sign up to set email alerts
|

Predictive factors of long-term survival in the octogenarian undergoing surgical aortic valve replacement: 12-year single-centre follow-up

Abstract: The improvement of life expectancy created more surgical candidates with severe symptomatic aortic stenosis and age >80. Therefore, the main objective of this observational, retrospective single-centre study is to compare the long-term survival of octogenarians that have undergone surgical aortic valve replacement (AVR) to the survival of the general population of the same age and to establish whether any perioperative characteristics can anticipate a poor long-term result, limiting the prognostic advantage of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 17 publications
0
6
1
Order By: Relevance
“…Our reported 30-day mortality for iAVR (4.5%) and AVR + CABG (6.5%) are lower than in-hospital mortality reported by other investigators during the last decade [10,11,16,29].…”
Section: Discussioncontrasting
confidence: 67%
See 2 more Smart Citations
“…Our reported 30-day mortality for iAVR (4.5%) and AVR + CABG (6.5%) are lower than in-hospital mortality reported by other investigators during the last decade [10,11,16,29].…”
Section: Discussioncontrasting
confidence: 67%
“…Longer duration of CPB and X-Clamp are always a concern, particularly in the elderly, as longer CPB is associated with increased incidence of cerebral, renal and coagulation damage, and greater X-Clamp predisposes to increased risk of myocardial damage. Cappabianca [16] reported that the duration of CPB time (OR 1.02, p = 0.004) was an independent predictor of in-hospital mortality, while Dell'Amore [19] observed that a shorter X-Clamp time had a protective role (OR 0.8, p = 0.01).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7,8,[10][11][12][13][14][15] However, the impact of preoperative paroxysmal AF in these patients is less well known. Namely, earlier studies included only patients with permanent AF 2,13,16 or patients with paroxysmal and permanent AF, were pooled. 4,14,17 Thus, the prognostic significance of paroxysmal AF has remained elusive.…”
mentioning
confidence: 99%
“…As there is no medical treatment for aortic stenosis besides vasodilators and diuretics for acute decompensation, the mainstay of treatment for aortic stenosis is still surgical or interventional aortic valve replacement [6, 10]. Ongoing inflammation in the circulatory system and increased shear stress has also been associated with endothelial dysfunction [11, 12].…”
Section: Introductionmentioning
confidence: 99%